ANALISIS COLLABORATIVE GOVERNANCE DALAM PENANGGULANGAN BENCANA DI KOTA PADANG (STUDI PADA BPBD PROVINSI SUMATERA BARAT) - Iqra' Syahadatul Aisyah; Syarifah Hidayatuzzahra; Zahra Meisya Saharyani; Boni Saputra (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study is motivated by the high level of disaster vulnerability in Padang City, which requires an effective, integrated, and multi-stakeholder disaster management system. The collaborative governance approach is essential in addressing the complexity of disaster issues that cannot be handled sectorally. This research aims to analyze the implementation of collaborative governance in disaster management in Padang City through the role of the Regional Disaster Management Agency of West Sumatra Province. This study employs a qualitative descriptive method with data collected through interviews and documentation. The results indicate that collaboration involves multiple cross-sector actors through a pentahelix approach, with the disaster management agency acting as coordinator, implementer, and commander in all disaster phases. The collaboration mechanism is carried out through an emergency command system, cluster-based role division, and formal inter-agency cooperation. However, the implementation is not yet optimal due to coordination challenges, differences in operational procedures among institutions, and low community participation. Therefore, strengthening cross-sector coordination, improving community capacity, and developing sustainable collaborative forums are necessary to enhance the effectiveness of disaster management in the future. Keywords: collaborative governance, disaster management, BPBD, pentahelix, coordination